Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1108/13552559910293146
|View full text |Cite
|
Sign up to set email alerts
|

Organisational learning: research issues and application in SME sector firms

Abstract: Over the last two decades the UK Government has massively expanded support for SME sector firms. Two important elements of this expansion have been the funding of intervention by commercial consultants and the provision of training schemes covering start-ups, owner-manager development and employee skills acquisition. Argues that a fresh approach is required which ensures embedding of the concept that firms should be more self-responsible and continually strive to find ways of enhancing their performance. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 9 publications
0
47
0
10
Order By: Relevance
“…Hence, they can be considered as a dynamic capability, given that they are a learned and stable pattern of collective activity through which the organization pursuits the improvement of effectiveness (Zollo & Winter, 2002). The mediating role of TDCs in the influence of OL on PERF becomes obvious via the quantification of the indirect effect (.178), which suggests that the relationship between OL and PERF cannot be very direct and is mediated by other variables, as Chaston et al (1999a) indicated. The results imply that while TDCs are an important direct driver of performance, it also appears to be a necessary mediator of the link between OL and PERF.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hence, they can be considered as a dynamic capability, given that they are a learned and stable pattern of collective activity through which the organization pursuits the improvement of effectiveness (Zollo & Winter, 2002). The mediating role of TDCs in the influence of OL on PERF becomes obvious via the quantification of the indirect effect (.178), which suggests that the relationship between OL and PERF cannot be very direct and is mediated by other variables, as Chaston et al (1999a) indicated. The results imply that while TDCs are an important direct driver of performance, it also appears to be a necessary mediator of the link between OL and PERF.…”
Section: Discussionmentioning
confidence: 94%
“…Some authors such as Chaston, Badger, and Sadler-Smith (1999a) maintain that OL is a path for achieving competitive advantage and helping organizations to become more innovative and improve their performance. Distinctive competencies are developed through the OL process, with this process, together with its outcomes forming a ''metalearning'' system.…”
Section: Organizational Learning As a Determinant Of Technological DImentioning
confidence: 98%
“…Theories of organisational learning are derived predominately from large firms but a number of authors have recognised the potential of these concepts for entrepreneurial development (e.g. Chaston et al, 1999).…”
Section: Entrepreneurial Personality and Learningmentioning
confidence: 99%
“…En este sentido, Chaston et al (1999) sostienen que el aprendizaje organizativo es un camino para alcanzar la ventaja competitiva y ayudar a las organizaciones a convertirse en más innovadoras y mejorar su rendimiento. La innovación implica la generación y la implantación de ideas, de procesos o de productos nuevos.…”
Section: Cao E Innovación En Productounclassified